Comparison of adequate relief with symptom, global, and responder endpoints in linaclotide phase 3 trials in IBS-C. Issue 1 (February 2015) - Camilleri, Michael; Lembo, Anthony J; Lavins, Bernard J; MacDougall, James E; Carson, Robyn T; Williams, Valerie SL; Nelson, Lauren M; Shiff, Steven J; Currie, Mark G; Kurtz, Caroline B; Johnston, Jeffrey M
Background: Optimal clinical trial endpoints for irritable bowel syndrome with constipation (IBS-C) are uncertain. Objective: The objective of this article is to compare adequate relief (AR) to abdominal/bowel symptoms, global endpoints, and FDA and EMA responder criteria; and to use AR as an anchor to assess clinically meaningful change (CMC) in IBS-C symptoms. Methods: Using pooled 12-week data from two phase 3 linaclotide clinical trials, daily abdominal/bowel symptoms and weekly global assessments were correlated with AR. Symptom CMC thresholds were estimated using AR as an anchor. Agreement between AR and FDA/EMA responder criteria was assessed. Results: Correlations of AR with percentage change in abdominal symptoms, bowel symptoms, and global endpoints ranged from 0.48–0.54, 0.32–0.39, and 0.61–0.71, respectively. Using AR as an anchor, CMC thresholds were 29% improvement in abdominal pain, 29% improvement in abdominal discomfort, and 0.7/week increase in CSBMs, similar to thresholds for IBS-C responder endpoints recommended by the FDA and EMA. There was considerable agreement of weekly responder rates between AR and the FDA and EMA endpoints (on average, 70%–76% and 71%–82% of weeks with agreement, respectively). Conclusions: AR bridges IBS-C clinical trials, putting into perspective the disparate primary endpoints recommended by professional societies and regulatory authorities, and allowing researchers, practitioners, and regulators to compare trial results.